1997
DOI: 10.1038/eye.1997.216
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric cycloplegia: A new approach

Abstract: This study shows that use of proxymetacaine prior to cyclopentolate results in atraumatic cycloplegia in children. This can confer multiple benefits on the doctor-patient relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 3 publications
1
11
0
1
Order By: Relevance
“…As a result many children develop a negative association with the clinic, and become distressed and uncooperative before drop instillation and during subsequent examinations. To try to reduce this discomfort, previous instillation of the local anaesthetic proxymetacaine has been advocated in a single study,1 which reported significant benefit. However, this was a retrospective study, with the particular limitation of using parental recall of their child's distress a year previously, as the measure of the pain experienced with the use of cyclopentolate alone.…”
mentioning
confidence: 99%
“…As a result many children develop a negative association with the clinic, and become distressed and uncooperative before drop instillation and during subsequent examinations. To try to reduce this discomfort, previous instillation of the local anaesthetic proxymetacaine has been advocated in a single study,1 which reported significant benefit. However, this was a retrospective study, with the particular limitation of using parental recall of their child's distress a year previously, as the measure of the pain experienced with the use of cyclopentolate alone.…”
mentioning
confidence: 99%
“…16 The most commonly used agent is 0.5 and 1% cyclopentolate, which is a muscarinic antagonist that paralyzes the actions of the ciliary muscle. Although the topical administration of cyclopentolate is quite frequently used in clinical practice to achieve an accurate refraction, the exact influence on HOAs has not been sufficiently investigated in children.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that instillation of proxymetacaine hydrochloride 0.5% prior to cyclopentolate resulted in less traumatic cycloplegia in children [1]. This was further supported by a second study, which showed a significant reduction in the total discomfort with cyclopentolate administered after premedication with proxymetacaine, compared with the use of cyclopentolate instilled after placebo [2].…”
Section: Introductionmentioning
confidence: 79%